The Role of The Homeroom Teacher in The Formation of Morals Students of Class 3 KMI (Kulliyatul Mu'allimat Alislamiyah) at Modern Islamic Boardingschool Darussalam Gontor for Girls 2 Mantingan Ngawi Academic Year 2020-2021 - Nurul; Muwahidah; Syarifah Syarifah; Nari (Educan : Jurnal Pendidikan Islam, 2023)
Each class is a work unit that remains solitary, the expression "unit" here alludes to the way that each class has its own qualities. Each class is a different work unit that capabilities as a subsystem. To control understudies at KMI (kulliyatul-Mu'allimat-Al-Iislamiyyah) instructors are required who can figure out the qualities of female understudies and can foster the ethics of female understudies "homeroom educator". An ever increasing number of individuals will succeed in the event that they impart positive and commendable characters. Training ought to coordinate parts of mental development (information and abilities), full of feeling (interest, ability, flexibility), and psychomotor (coordinated abilities) as well as reinforcing good person. Instructing and preparing are only a couple of the obligations. In teaching required upkeep and extension in innovation and science. While preparing implies creating abilities in understudies. In light of these suppositions, the exploration plans to dissect how the development of female understudies' ethics in class 3 KMI (Kulliyatul Mua'allimat Al-Islamiyah), what is the job of the homeroom educator in the arrangement of female understudies' ethics in class 3 KMI. This exploration utilizes subjective techniques which incorporate meetings, perception, and documentation, which are situated at Pondok Present day Darussalam Gontor Putri, Grounds 2, Mantingan, Ngawi. The consequences of information handling show that the job of the homeroom educator in the development of ethics in class 3 KMI understudies is more powerful, with the fundamental undertaking of the homeroom instructor as a critical thinking expertise in making a homeroom climate together, so the progress of doing the gaining capability and the measures from the job of the homeroom educator shows the outcomes that the female understudies in the class work on their ethics.